Perbandingan Makna Semantik Bahasa Indonesia Dengan Bahasa Daerah Gorontalo - Nuramila Nuramila; Rolan K. Daud (STIKes Ibnu Sina Ajibarang, 2024)
Semantics plays an important role in linguistics, especially in terms of meaning or in other words, semantics is a branch of linguistics that studies the meaning of words. Semantic analysis refers to the user's language and culture. Even the same word can have different meanings or nuances of meaning when used. This difference in the meaning of words often causes differences and misunderstandings. In Indonesian there are words that are the same as the Gorontalo Regional Language. However, of course every word from the two languages has different meanings when viewed from a semantic perspective. This research uses a descriptive method to determine the comparison of Indonesian lexical meaning with Gorontalo language meaning. The location of this research was carried out at the BTN Pulubala Housing Complex, precisely in Pulubala Village, Central City, Gorontalo City. The data collection technique used by researchers is an open interview technique. From the research results, it was found that there are several words in Indonesian that are the same as the Gorontalo Regional Language, but have different meanings or semantic meanings.